ĐỊA TẦNG CỦA CÁC THÀNH TẠO TRẦM TÍCH MÀU ĐỎ TUỔI CRETA Ở MIỀN BẮC VIỆT NAM - Khiển, Nguyễn Xuân (Vietnam Journal of Earth Sciences, 2017)
The Cretaceous non-marine red-beds in North Vietnam have a very important position in the historyof development of the Earth’s crust on this territory. Based on the results of recent researches, the issues addressed in the paper provide a systematicoverview on the stratigraphy of the Creta ceous nonmarinered-beds in the study area. Among others, the paper emphasizes new data on bio- and lithostratigraphy that help to provide a more accurate estimation of the volume of stratigraphic units and their relation with relevant geological entities.